Ficolin B in Diabetic Kidney Disease in a Mouse Model of Type 1 Diabetes - Charlotte Berg Holt; Jakob Appel Østergaard; Esben Axelgaard; Gitte Krogh Nielsen; Yuichi Endo; Steffen Thiel; Troels Krarup Hansen (Hindawi Limited, 2015)
Background. The innate immune system may have adverse effects in diabetes and cardiovascular disease. The complement system seems to play a key role through erroneous complement activation via hyperglycaemia-induced neoepitopes. Recently mannan-binding lectin (MBL) was shown to worsen diabetic kidney changes. We hypothesize that mouse ficolin B exerts detrimental effects in the diabetic kidney as seen for MBL. Methods. We induced diabetes with streptozotocin in female wild-type mice and ficolin B knockout mice and included two similar nondiabetic groups. Renal hypertrophy and excretion of urinary albumin and creatinine were quantified to assess diabetic kidney damage. Results. In the wild-type groups, the kidney weighed 24% more in the diabetic mice compared to the controls. The diabetes-induced increase in kidney weight was 29% in the ficolin B knockout mice, that is, equal to wild-type animals (two-way ANOVA, P=0.60). In the wild-type mice the albumin-to-creatinine ratio (ACR) was 32.5 mg/g higher in the diabetic mice compared to the controls. The difference was 62.5 mg/g in the ficolin B knockout mice, but this was not significantly different from the wild-type animals (two-way ANOVA, P=0.21). Conclusions. In conclusion, the diabetes-induced effects on kidney weight and ACR were not modified by the presence or absence of ficolin B.